KASUNDAAN DALAM MOTIF BATIK RAGEN PANGANTEN - Riana, Irpan; Putra, Yuda Syah (Jurusan Seni Rupa ISBI Bandung, 2023)
The Ragen Panganten Batik motif is one of the Batik motifs created by Rd. Lalam Wiranatakusumah, produced by Batik Komar. The motif was reconstructed based on the ancient manuscript of Siksakandang Kares and the culture of the Sundanese people. In Ragen Panganten's batik motif, it has Kasundaan meaning and identity. Ragen Panganten's batik motif consists of various decorations, such as the stylization of the Julang bird, Wijayakusumah plants and Binokasih's crown, to the colors used that reflect Kasundaan's identity. The meaning that comes from the Ragen Panganten motif is a symbol of marriage. The Ragen Panganten Batik motif, which according to Sundanese cosmology has symbols of emptiness and content, encompasses a paradoxical dualistic nature. In addition, the Ragen Panganten batik motif is always based on a triangular shape or pattern. The significance of the triangular shape in Sundanese society is closely related to the tritangtu pattern, the life concept of the Sundanese people. Keywords: Kasundaan, Batik, Ragen Panganten, Rd. Lalam ———————————————————————————— Motif Batik Ragen Panganten merupakan salah satu motif Batik yang dibuat oleh Rd. Lalam Wiranatakusumah, yang di produksi oleh Batik Komar. Motif tersebut direkonstruksi berdasarkan naskah kuno Siksakandang Karesian dan budaya masyarakat Sunda. Dalam batik motif Ragen Panganten memiliki makna dan identitas Kasundaan. Motif batik Ragen Panganten yang terdiri dari ragam hias yang seperti stilasi burung Julang, Tumbuhan Wijayakusumah dan Mahkota Binokasih sampai dengan warna yang dipakai mencerminkan identitas Kasundaan. Makna yang muncul dari motif Ragen Panganten merupakan simbol dari perkawinan. Motif Batik Ragen Panganten, memiliki simbol dari kosong dan isi, dalam pandangan kosmologi Sunda termasuk sifat dualistik yang paradoks. Selain itu, motif batik Ragen Panganten selalu dilandasi dari bentuk atau pola segitiga. Makna bentuk segitiga dalam masyarakat Sunda erat kaitannya dengan pola tritangtu yang merupakan konsep kehidupan masyarakat Sunda. Kata Kunci : Kasundaan, Batik, Ragen Panganten, Rd. Lalam